Perbandingan Kurikulum Bahasa Mandarin di Beberapa Negara ASEAN (Association of Southeast Asian Nations) - Adinda Aisyah; Gina Amelia; Lubnah Latifatus Syarof; Nasya Al Zahra; Rahayu Nurfadillah; Rahmah Nur Syifa (Semantik : Jurnal Riset Ilmu Pendidikan, Bahasa dan Budaya, 2025)
This research discusses the comparison of Mandarin curriculum in six ASEAN member countries, namely Indonesia, Malaysia, Singapore, Thailand, Vietnam and the Philippines. Mandarin is increasingly considered strategic in the ASEAN region as economic, educational and cultural ties with China increase. However, teaching approaches and curriculum policies in each country show significant variations. This research uses the literature review method to analyze the policies, curriculum structure, teaching methods, and challenges faced in each country. The results show that Singapore and Malaysia have the most structured and responsive approaches, while countries such as Indonesia and the Philippines still face various barriers in the provision of learning infrastructure and teaching staff. This study recommends the importance of regional collaboration in the development of curriculum standards, teacher training, and the development of contextualized teaching materials so that the quality of Chinese language learning in the ASEAN region can be improved equally.